Bridging the research-practice gap in healthcare: a rapid review of research translation centres in England and Australia - Tracy Robinson; Cate Bailey; Heather Morris; Prue Burns; Angela Melder; Charlotte Croft; Dmitrios Spyridonidis; Halyo Bismantara; Helen Skouteris; Helena Teede (BMC, 2020)
Abstract Background Large-scale partnerships between universities and health services are widely seen as vehicles for bridging the evidence-practice gap and for accelerating the adoption of new evidence in healthcare. Recently, different versions of these partnerships - often called academic health science centres - have been established across the globe. Although they differ in structure and processes, all aim to improve the integration of research and education with health services. Collectively, these entities are often referred to as Research Translation Centres (RTCs) and both England and Australia have developed relatively new and funded examples of these collaborative centres. Methods This paper presents findings from a rapid review of RTCs in Australia and England that aimed to identify their structures, leadership, workforce development and strategies for involving communities and service users. The review included published academic and grey literature with a customised search of the Google search engine and RTC websites. Results RTCs are complex system-level interventions that will need to disrupt the current paradigms and silos inherent in healthcare, education and research in order to meet their aims. This will require vision, leadership, collaborations and shared learnings, alongside structures, processes and strategies to deliver impact in the face of complexity. The impact of RTCs in overcoming the deeply entrenched silos across organisations, disciplines and sectors needs to be captured at the systems, organisation and individual levels. This includes workforce capacity and public and patient involvement that are vital to understanding the evolution of RTCs. In addition, new models of leadership are needed to support the brokering and mobilisation of knowledge in complex organisations. Conclusions The development and funding of RTCs represents one of the most significant shifts in the health research landscape and it is imperative that we continue to explore how we can progress the integration of research and healthcare and ensure research meets stakeholder needs and is translated via the collaborations supported by these organisations. Because RTCs are a recent addition to the healthcare landscape in Australia, it is instructive to review the processes and infrastructure needed to support their implementation and applied health research in England.